Cryopreservation of sperm of the Adriatic grayling (Thymallus thymallus) and the marble trout (Salmo marmoratus) from the Soča river in Slovenia - Horváth, Ákos; Jesenšek, Dušan; Snoj, Aleš; Csorbai, Balázs; Bokor, Zoltán; Urbányi, Béla (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2014)
A cryopreservation protocol was tested on the sperm of genetically distinct Adriatic grayling (Thymallus thymallus) and the Natura2000-listed marble trout (Salmo marmoratus) from the Soča River basin in Slovenia. Sperm was frozen in an extender composed of 200 mM glucose, 40 mM KCl, 30 mM Tris (pH 8.0) and 10% methanol as a cryoprotectant in the vapour of liquid nitrogen. Sperm dilution ratios of 1:1, 1:4 and 1:9 were tested. The cooling rate was 57 ± 1°Cmin-1 in all cases. In the grayling, the highest ratio of eyed eggs (74 ± 4 % vs. 69 ± 6 % in the control) and the highest hatch percentage (63 ± 6 % vs. 56 ± 10 % in the control) was observed with a dilution ratio of 1:1. In the marble trout, the highest percentage of eyed eggs (84 ± 4 % vs. 88 ± 3 in the control) and the highest hatch rate (70 ± 3 % vs. 76 ± 2 % in the control) was again found using the 1:1 dilution ratio of the sperm. In both species, individual sperm samples had a significant effect on the results. Sperm-to-egg ratios ranging from 2.5 to 5.7 × 104 spermatozoa per egg yielded satisfactory hatch rates (67 ± 7 % to 73 ± 7 %) in the grayling.